2014
DOI: 10.1038/sc.2014.184
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysfunction and chronic inflammation following spinal cord injury

Abstract: Study design: Review article. Objectives: The objective of this study is to provide an overview of the many factors that contribute to the chronic inflammatory state typically observed following spinal cord injury (SCI). Methods: Literature review. Results: Not applicable. Conclusion: SCI is typically characterized by a low-grade inflammatory state due to a number of factors. As bidirectional communication exists between the nervous, endocrine and immune systems, damage to the spinal cord may translate into bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 52 publications
7
114
0
1
Order By: Relevance
“…Some scholars have confirmed the role of an immunoinflammatory response in SCI and its repair process through animal experiments [26,27]. In addition, some studies have proposed intervening in the immunoinflammatory response to promote interventions after SCI [28].…”
Section: Discussionmentioning
confidence: 97%
“…Some scholars have confirmed the role of an immunoinflammatory response in SCI and its repair process through animal experiments [26,27]. In addition, some studies have proposed intervening in the immunoinflammatory response to promote interventions after SCI [28].…”
Section: Discussionmentioning
confidence: 97%
“…The migrating and invading macrophages represent an integral and specific feature, since the sequential activation and composition of pro-inflammatory M1 macrophages and alternatively stimulated M2a, M2b, and M2c macrophage subtypes occur during wound healing and facilitate the transition between inflammation, proliferation, and tissue remodeling [22]. Generally, SCI induces a low-grade inflammatory state which is characterized by bidirectional communication between the nervous, endocrine, and immune system [30]. Microglia accumulation peaks in the lesion on 3-7 days post SCI throughout the gray and white matter at the epicenter of the injury site [31].…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that inflammatory cascade might serve the potential molecular mechanisms underlying the pathogenesis of cervical spondylotic myelopathy, leading to migraine attack. Second, increased inflammation in the cervical spine due to the proinflammatory molecules release into the bloodstream upregulated the hypothalamicpituitary-adrenal axis, causing the hypothalamic dysfunction 32 . This process intensified the sensitivity to pain in the brain, which may lead to predisposition to migraine.…”
Section: Discussionmentioning
confidence: 99%